2017
DOI: 10.1016/j.ijcard.2017.02.130
|View full text |Cite
|
Sign up to set email alerts
|

Phenotypic expression of ARVC: How 12 lead ECG can predict left or right ventricle involvement. A familiar case series and a review of literature

Abstract: ARVC may lead to an extreme phenotypic variability in clinical manifestations even within patients coming from the same family in which ARVC is caused by the same genetic mutation. ECG progression over time reflects disease evolution and in particular cases may anticipate wall motion abnormalities by years.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 49 publications
1
3
0
Order By: Relevance
“…More recent genotype-phenotype correlation studies have shown early and greater LV involvement related to some genetic defects, such as desmoplakin-gene mutations. 28 The present study extended previous observations [25][26][27] by showing that the electrocardiographic pattern of low QRS voltages may predict LV involvement in the context of ACM with a specificity of 100%, although its sensitivity did not exceed 30%. The mechanism involved in the reduction of QRS voltages reasonably consists of the decrease of LV myocardial mass, which mostly accounts for the generation of the electrical activity causing the depolarization current responsible for the QRS complex.…”
Section: Low Qrs Voltages In Limb Leadssupporting
confidence: 86%
See 1 more Smart Citation
“…More recent genotype-phenotype correlation studies have shown early and greater LV involvement related to some genetic defects, such as desmoplakin-gene mutations. 28 The present study extended previous observations [25][26][27] by showing that the electrocardiographic pattern of low QRS voltages may predict LV involvement in the context of ACM with a specificity of 100%, although its sensitivity did not exceed 30%. The mechanism involved in the reduction of QRS voltages reasonably consists of the decrease of LV myocardial mass, which mostly accounts for the generation of the electrical activity causing the depolarization current responsible for the QRS complex.…”
Section: Low Qrs Voltages In Limb Leadssupporting
confidence: 86%
“…24 Several studies reported anecdotal evidence that low QRS voltages in limb leads may reflect the presence of a segmental LV scar/ LGE, which can be evidenced by CE-CMR. [25][26][27] Actually, CE-CMR has emerged as the imaging test that allows the "in vivo" detection and the characterization of LV involvement in ACM, in terms of dilatation and systolic dysfunction assessed by cine CMR sequences and/or fibrofatty scar detected by postcontrast CMR sequences. 7 On the basis of the presence and extent of the coexistent LV involvement, the spectrum of ACM phenotypes has broadened to include "biventricular" and "left-dominant" variants, in addition to the classic "right-dominant" form.…”
Section: Low Qrs Voltages In Limb Leadsmentioning
confidence: 99%
“…( A , B ) CMR of a patient with DSC2 p.Arg49His mutation showing biventricular involvement in the LGE mode (red arrows); ( C ) 12-lead ECG showing a reduction of R waves amplitude in left precordial leads (left involvement) and inverted T waves in V1-V6 (RV strain pattern); together they indicate biventricular involvement. Reproduced with permission from Gaido et al (2017) [ 37 ].…”
Section: Figurementioning
confidence: 99%
“…Gandjbakhch et al 17 also described this variant as a consequence of de novo occurrence. Gaido et al 18 suggested that ARVC patients may exhibit extreme phenotypic-variavility in their clinical manifestations, even among patients carrying thep.Arg49His in the same family.
Fig. 2Summary of the DSG2 variants found in the with ARVC.As determined using Human GRCh37/hg19, NM_001943.4:c.146G>A/p.
…”
mentioning
confidence: 99%